Effects of hydraulic loading rate and substrate on ammonium removal in tidal flow constructed wetlands treating black and odorous water bodies. (February 2021) - Zhang, Quan; Yang, Yongqiang; Chen, Fanrong; Zhang, Lingling; Ruan, Jingjun; Wu, Shijun; Zhu, Runliang
Graphical abstract: Highlights: A maximum hydraulic loading rate of 4 m·d −1 was employed in TFCWs. Zeolite-augmented TFCW enhanced the removal efficiencies of NH4 + -N and TN. Adding zeolite changed the microbial community structure and nitrifier's diversity. Zeolite addition increased nitrification genes but not denitrification genes. TFCW-Z is a promising alternative for treating black and odorous water bodies. Abstract: The efficient removal of ammonium nitrogen (NH4 + -N) is vital to eliminating black and odorous water bodies. In this work, tidal flow constructed wetlands with gravel (TFCW-G) and with a mixture of zeolite and gravel (TFCW-Z) were set up to treat black and odorous water bodies at different hydraulic loading rates (HLRs). Results showed that zeolite significantly enhanced nitrogen removal, and the maximum NH4 + -N removal efficiency of 96.69% was achieved in TFCW-Z at HLR of 3 m·d −1 with a flooding and drying cycle of 2 h. Zeolite addition changed the microbial community structure and the abundance of nitrification genes. Comammox Nitrospira was the only enriched strain accounting for NH4 + -N removal in TFCW-G, while the co-occurrence of comammox Nitrospira and the canonical and potential ammonia-oxidizing bacteria were identified in TFCW-Z. Summarily, high performance, together with low footprint and low maintenance cost, are characteristics that make the TFCW-Z a promising and competitive alternative.